Sensors in blockchain. Issue 2 (February 2022) - Altay, Alara; Learney, Robert; Güder, Firat; Dincer, Can
Abstract : Blockchain, the technology behind bitcoin, has stimulated global conversation around digital decentralization to connect societies and economies. Connected low-cost sensors within Internet of Things (IoT) networks may soon perform measurements, exchange data, and make decisions automatically over decentralized networks; these systems could improve healthcare, the quality of goods, and supply chain efficiency.